Impact of postcolectomy adhesion-related complications on healthcare utilization - Etter K; Sutton N; Wei D; Yoo A (Dove Medical Press, 2018)
Katherine Etter,1 Nadia Sutton,2 David Wei,3 Andrew Yoo3 1Medical Devices-Epidemiology, Johnson and Johnson, Raynham, MA 02767, USA; 2Ethicon HEMA, Somerville, NJ 08876, USA; 3Medical Devices-Epidemiology, Johnson and Johnson, New Brunswick, NJ 08901, USA Objective: The objective of this study was to explore adhesion-related complications (ARCs) within 1 year after colectomy.Methods: Using Truven MarketScan® Commercial and Medicare databases, the first inpatient colectomies during 2009–2013 (index) were identified: left, right, partial, transverse, or total. One-year continuous enrollment was required pre and postindex. Only the first inpatient rehospitalization event was analyzed. ARC was defined as the subset of rehospitalizations with a diagnosis of ileus, small bowel obstruction, or postindex adhesiolysis. ARC and non-ARC events were evaluated descriptively, including time to ARC, length of stay (LOS), and total hospitalization reimbursement (2015 US dollars [2015 USD]). Patient, provider, and procedure factors associated with ARC were explored using logistic regression models.Results: A total of 64,532 colectomies were identified: left (39.2%), right (34.9%), partial (20.0%), transverse (2.3%), and total (3.6%). Surgical approach was classified as open (60.1%) and laparoscopic (39.9%). All-cause first inpatient readmission incidence within 1 year was 24.7%, and ARC incidence was 5.7% in all patients or 23.2% in all first readmissions. ARC had statistically higher resource utilization compared to non-ARC with respective mean (SD) time to event (130 [102] and 137 [106] days), mean (SD) LOS (7.2 [8.0] and 5.2 [6.8] days), and mean (SD) total reimbursement ($29,802 [$43,037] and $22,476 [$36,130]). ARC risk factors included (OR [95% CI]) resection type (total vs right, 3.78 [3.27–4.36]), left vs right (1.69 [1.53–1.86]), adhesiolysis (2.45 [1.42–4.23]), computerized tomography (1.79 [1.65–1.95]), surgical indication: inflammatory bowel disease vs cancer (1.69 [1.43–1.99]), and multiple abdominal procedures (1.38 [1.29–1.49]). Laparoscopic approach was protective (0.42 [0.39–0.46]).Conclusion: ARCs were associated with almost one-fourth of all first rehospitalizations within the first year after colectomy and were associated with substantial healthcare utilization. Risk factors included increased index colectomy complexity, while the laparoscopic approach was protective. Future research is needed to better identify high-risk patients and allow for appropriate economic and clinical risk adjustment of outcomes. Keywords: bowel obstruction, ileus, rehospitalization